THREAT TO NYONYA CUISINE HERITAGE SUSTAINABILITY IN MALAYSIA: A SYSTEMATIC LITERATURE REVIEW APPROACH - Sakinah Haniff; Siti Ida Isnainie Md Mubin; Mohamad Farhan Azmi; Wan Rusni Wan Ismail (Journal of Islamic, Social, Economics and Development, 2022)
With rich gastronomic culture, Malaysia offers a wide variety of cuisines with unique heritage background and identity. Nyonya cuisines for instance emerged from acculturation process of two distinctive culture hence creating unique cuisines that only can be found in certain location in Malaysia. This systematic review article focuses on the current state of literature related to the development of Nyonya cuisine in Malaysia and aims of this review is to identify the gap in the literature. This research follows Preferred Reporting Items for Systematic Review and MetaAnalysis 2020 (PRISMA - 2020) methodology. This systematic literature review relies heavily on two major journal databases, Science Direct and Scopus. Indirectly, a total of 14 articles have met the standards to be reviewed systematically. Finally, the review successfully summarized six threats to Nyonya Cuisine Heritage sustainability in Malaysia: weak roles of society, modernization, globalization, tough competition from larger mainstream ethnic restaurants, halal status, and cost of living.